Mechanisms of immune evasion of monkeypox virus - Zandi, Milad; Shafaati, Maryam; Hosseini, Fatemeh (Frontiers in Microbiology, 2023)
The monkeypox epidemic in 2022 provided a good opportunity to study the immune profiles of monkeypox virus. However, inflammatory cytokines such as IFNγ and TNFα can be released by CD4+ and CD8+ T cells, which are specific for monkeypox virus. monkeypox virus also has no effect on the expression of MHC classes. Cells infected with monkeypox virus can prevent T cells from being activated via their T cell receptors. Insensitivity is an MHC-independent strategy for controlling antiviral T cells activation and inflammatory cytokines production. It is likely a critical aspect of virus spread in the infected host. The ability of monkeypox virus to spread efficiently as cell-associated viremia may be explained by the evasion strategies employed by the virus to subvert immunological surveillance by virus-specific T cells.